Multivariate fractional representation formula and Ostrowski type inequality - Anastassiou, George A. (Sarajevo Journal of Mathematics, 2024)
Here we derive a multivariate fractional representation formula involving ordinary partial derivatives of first order. Then we prove a related multivariate fractional Ostrowski type inequality with respect to uniform norm.